The Effect of Rigging Angle on Longitudinal Direction Motion of Parafoil-Type Vehicle: Basic Stability Analysis and Wind Tunnel Test - Takahiro Moriyoshi; Kazuhiko Yamada; Hiroyuki Nishida (International Journal of Aerospace Engineering)
The paraglider, a flexible flying vehicle, consists of a parafoil with flexible wings, suspension lines, and a suspended payload. At this time, the suspension lines have several parameters to be designed. Above all, a parameter called Rigging Angle (RA) is sensitive to the aerodynamic characteristics of a paraglider during flight. In this study, the effect of RA is clarified using the two-dimensional stability analysis and a wind tunnel test. The mechanisms about the parafoil-type vehicle stability are clarified through the experimental and analytical approaches as follows. The RA has an allowable range for a stable flight. When the RA is set out of the range, the parafoil cannot fly stably. Furthermore, the behavior of the parafoil wing in the case of lower RA than the allowable range is different from the case of higher RA. The parafoil collapses from the leading edge of the canopy and cannot glide in the case of lower RA.